Development of a REBa2Cu3O7−δ multi-core superconductor with 'inner split' technology. (3rd March 2016) - Jin, Xinzhe; Oguro, Hidetoshi; Oshima, Yugo; Matsuda, Tetsuro; Maeda, Hideaki
Abstract: Recently, advanced research into fine filament technology for tape-shaped superconducting-coated conductors composed of REBa2 Cu3 O7– δ (RE123, RE: rare earth such as Gd or Y, 0 < δ < 1) has been carried out to improve performance in high magnetic fields by reducing the large diamagnetism of the RE123 superconducting layer. The major challenge for high-field NMR/MRI applications is to obtain high tensile stress tolerance above 500 MPa with a high critical current. In this study, a RE123 multi-core superconductor was fabricated via an 'inner split' method using a commercially available RE123 single-core coated conductor, where only the ceramics (RE123 and buffer layers) in wire are electrically separated to multi-filaments without superconducting current flow between the filaments. Experimental results show that wires having 2, 3, 4, or 5 cores have a high critical current (above 95% of the original) and maintain tensile stress tolerance above 650 MPa. The diamagnetism of the five-core wire is reduced ∼85% of the original at 7 T. Thus, the wire was optimized via inner split method for high-field use.